Spread of antibiotic resistance genes and microbiota in airborne particulate matter, dust, and human airways in the urban hospital. (August 2021) - Zhou, Zhen-Chao; Liu, Yang; Lin, Ze-Jun; Shuai, Xin-Yi; Zhu, Lin; Xu, Lan; Meng, Ling-Xuan; Sun, Yu-Jie; Chen, Hong
Graphical abstract: Highlights: Dust contained diverse antibiotic resistance genes (ARGs) and microbes. Airborne particulate matter contained high total relative abundance of ARGs. Campylobacter spp . positively correlated with fluoroquinolone resistance genes. Staphylococcus spp. positively correlated β-lactams ( bla Z, mec A) resistance genes. Microbes and ARGs in particulate matter posed high risks to patient airways. Abstract: Antimicrobial resistance is an increasingly serious threat to public health worldwide. The presence of antibiotic resistance genes (ARGs) in human airways and relevant environments has not received significant attention. In this study, abundances of ARGs and microbes from airborne particulate matter, dust, and human airways in a hospital were profiled using high-throughput qPCR and 16S rRNA gene sequencing. More diverse ARGs and microbes in indoor dust and higher levels of ARGs in particulate matter PM10 and PM2.5 were observed. Macrolides and aminoglycoside resistance genes were the most abundant ARGs in the airway and environmental samples, respectively. Moreover, the co-occurrences of priority pathogens, ARGs, and mobile genetic elements (MGEs) were shown by the Network analysis. Campylobacter spp . and Staphylococcus spp. positively correlated with fluoroquinolone ( vat C-02, mex D) and β-lactams ( bla Z, mec A) resistance genes, respectively. In this regard, based on SourceTracker analysis, inhalable particles contributed to 4.0% to 5.5% of ARGs in human airway samples, suggesting an important exchange between airborne inhalable particles and human commensals. This study may advance knowledge about ARGs in airborne particulate matter and dust associated environments, reveal their potential link between environments and humans, and provide a new sight and fundamental data for ARG risk assessment.